Rights, Indigeneity, and the Market of Rastafari. Issue 1 (14th March 2017) - Lewis, Jovan Scott
Abstract: This article is concerned with the ways in which discourses of rights serve to destabilize indigenous logics when used for gains in the market. It does so through examining a Rastafarian tour group who uses their participation in the tourism market to challenge what they believe are infringed cultural property rights. As a means of commercially defending these rights, the group employs a discourse of indigeneity. In this process, they have gained partial recognition from the World Intellectual Property Organization and increasing acknowledgement from the Jamaican government. However, while the basis of indigeneity strongly supports the case of intellectual and cultural property rights, this recognition ultimately further identifies the group, and Rastafari in general, with Jamaica.